A surface plasmon resonance sensor based on a single mode D-shape polymer optical fiber. (23rd December 2016) - Gasior, Katarzyna; Martynkien, Tadeusz; Napiorkowski, Maciej; Zolnacz, Kinga; Mergo, Pawel; Urbanczyk, Waclaw
Abstract: For the first time to our knowledge, we report a successful fabrication of surface plasmon resonance (SPR) sensors in a specially developed single-mode birefringent polymer D-shape fiber with a core made of PMMA/PS copolymer. A small distance between the core and the cladding boundary allows to deposit a gold layer directly onto the flat fiber surface, which significantly simplifies the sensors fabrication process. The developed SPR sensor exhibits a sensitivity of 2765 nm RIU −1 for the refractive index of external medium equal to 1.410, which is similar to the sensitivity of the SPR sensors based on conventional side-polished single-mode silica fibers. Using the finite element method, we also numerically studied the sensor performance. The sensor characteristics obtained in the simulations are in a relatively good agreement with the experimental results.